ANALISIS PENERAPAN PRINSIP 5R (RINGKAS, RAPI, RESIK, RAWAT, RAJIN) DI BENGKEL X, KECAMATAN MLATI, KABUPATEN SLEMAN, YOGYAKARTA - Damairia Hayu Parmasari; Budi Sulistyo Nugroho (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Background: 5R (Ringkas, Rapi, Resik, Rawat, dan Rajin) is a work culture that must be applied in all workplaces in both the formal and informal sectors. The application of the 5R aims to make workers feel comfortable and safe when working. Besides, the application of the 5R can make work more effective and efficient because it can eliminate time wasted because more time to search for goods, work areas that look full due to overload of equipment and goods that are not needed or dirty environment. Machine shop X in Mlati Subdistrict, Sleman, Yogyakarta is one of the informal sectors that has not implemented 5R. This can be seen from the condition of the work area which is full of unnecessary, messy, and dirty equipment and goods. Therefore researchers researched the analysis of the application of 5R in Machine shop X. Objectives: The purpose of the study was to find out the application of the 5R principle in Machine shop X. Methods: This research design qualitative design. The research was conducted by direct observation and using the 5R checklist. Research results: The results showed that the application of 5R in Machine shop X was still poor. This can be seen from the achievement of the overall 5R which is below 50%. Conclusion: The research concludes that the implementation of the 5R in Machine shop X is still poor so that training on 5R and internal audits is needed periodically.Keywords: Implementation, 5R, machine shop